2002
DOI: 10.1038/sj.sc.3101317
|View full text |Cite
|
Sign up to set email alerts
|

The Tetrafigap Survey on the long-term outcome of tetraplegic spinal cord injured persons: Part III. Medical complications and associated factors

Abstract: Study design: To study the short-and long-term medical complications encountered in tetraplegic spinal cord injured persons (TSCI) and to give prominence to both the medical and socio-economic factors with which they are respectively associated. Methods: The Tetra®gap Study is a multicentre epidemiological survey carried out using selfadministered questionniares studying the global long-term outcome of TSCI patients after the initial phase of rehabilitation. Results: The data for 1668 patients were analyzed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 36 publications
4
50
0
3
Order By: Relevance
“…The Tetrafigap survey of patients with tetraplegia reported contractures in 84.7% of respondents. 20 In the present study, at least one contracture was observed in 17.3% of subjects with NTSCL. The contractures interfere with performance of motor tasks, contribute to spasticity and result in deformity.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The Tetrafigap survey of patients with tetraplegia reported contractures in 84.7% of respondents. 20 In the present study, at least one contracture was observed in 17.3% of subjects with NTSCL. The contractures interfere with performance of motor tasks, contribute to spasticity and result in deformity.…”
Section: Discussionsupporting
confidence: 54%
“…Similarly, 36.5% of subjects in Tetrafigap study also had this complication. 20 In the present study 31% of subjects with NTSCL had constipation. This could be due to immobility, changes in colonic compliance, prolonged transit time, fecal impaction, poor fluid intake and low fiber content in diet.…”
Section: Discussionsupporting
confidence: 48%
“…7,12,13 The reason could be the decrease in plasticity of the central nervous system with age, as far as neurogenic pain is concerned, as well as overuse of supra-lesional joints leading to osteo-articular pains. 14 Another factor could be psycho-social stresses. 10 Pain in the back and chest was seen in all the groups especially in the group that were 1-o6 months after injury.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The reported prevalence of pressure ulcers among spinal cord-injured manual wheelchair users (MWUs) ranges from 14 to 85%, and the most common site is the ischial tuberosity. [4][5][6] In sitting, the study showed that 18% of the body weight is distributed over each ischial tuberosity region. 7 Able-bodied people are able to sense physical discomforts associated with prolonged sitting and are able to reposition their body positions frequently, thereby protecting their tissues from ischemic damage.…”
Section: Introductionmentioning
confidence: 99%